2019
DOI: 10.4049/jimmunol.1801258
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methylation Directs Myeloid TLR4 Expression and Regulates Wound Healing following Cutaneous Tissue Injury

Abstract: Myeloid cells are critical for orchestrating regulated inflammation during wound healing. TLRs, particularly TLR4, and its downstream-signaling MyD88 pathway play an important role in regulating myeloid-mediated inflammation. Because an initial inflammatory phase is vital for tissue repair, we investigated the role of TLR4-regulated, myeloid-mediated inflammation in wound healing. In a cutaneous tissue injury murine model, we found that TLR4 expression is dynamic in wound myeloid cells during the course of nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…This switch is significantly impaired in obesity/T2D and results in chronic inflammation and nonhealing wounds; however, the etiology is unclear. We and others have previously identified that chronic inflammation in diabetic wounds is governed by epigenetic regulation of macrophages (12)(13)(14)(15)(16). In this study, we identify that the HAT MOF regulates inflammation in macrophages during normal and diabetic wound repair.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…This switch is significantly impaired in obesity/T2D and results in chronic inflammation and nonhealing wounds; however, the etiology is unclear. We and others have previously identified that chronic inflammation in diabetic wounds is governed by epigenetic regulation of macrophages (12)(13)(14)(15)(16). In this study, we identify that the HAT MOF regulates inflammation in macrophages during normal and diabetic wound repair.…”
Section: Discussionsupporting
confidence: 49%
“…Wounds were then carefully minced with sharp scissors and digested by incubating in a solution of 50 mg/mL Liberase TM (Roche) and 20 U/mL DNase I (Milli-poreSigma). Because the final cell number is limited, wounds from the same genotype/treatment were pooled to maximize cell yield, as previously published (11,12,14,16,54,(57)(58)(59). Wound cell suspensions were then gently plunged and filtered through a 100-μm filter to yield a single-cell suspension.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Major surgery induces rapid changes in DNA methylation in genes associated with the inflammatory response and wound healing, including C‐reactive protein and IL‐6 99,100 . It is recognized that these shifts in methylation may contribute to surgical complications including infection and delirium 99,101,102 …”
Section: Micrornasmentioning
confidence: 99%